Public Works Concession Delimitation from other Contracts - Bularca Anca Roxana (Tribuna Juridică, 2012)
The concession of public services without the concession of the related public works was viewed as an exception. The public services contract was considered to rank first among the administrative contracts. The European Court of Justice ruled that establishing of the nature of a contract – whether it is a public works contract or a public contract of a different nature – is made by identifying the main purpose of the contract that determines the applicable directive, including situations where the contract has elements regarding the concession of public works as well as other types of public contracts. Also, the concept of concession used in relation to both concession and PPP was deemed in Romania as a source of confusion and ambiguity regarding the confidence of both the public and private partner within the context of project development.